PENGARUH CITRA MEREK DAN PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PRODUK KANTONG PLASTIK TOMAT - Sugiyanto; Robert Aprioman (GoAcademica Research dan Publishing, 2021)
The purpose of this study was to analyze the effect of brand image and promotion on consumer loyalty with satisfaction as an intervening variable on tomato plastic bag products. This type of research uses associative research. The data source used is the primary data source. In this study the dependent variable is loyalty (Y), the independent variable is brand image (X1) and promotion (X2), and the intervening variable is consumer satisfaction (Z). The data test in this study consisted of a validity test, a reliability test and a path analysis test. Based on the analysis of the research data, it can be concluded that: 1) Brand Image (X1) and Promotion (X2) affect satisfaction (Z); 2) Brand Image (X1) and Promotion (X2) affect Loyalty (Y); 3) Satisfaction (Z) has an effect on Loyalty (Y); and 4) Brand Image (X1) and Promotion (X2) have an influence on consumer loyalty through consumer satisfaction of Tomato brand Plastic Bag Products.